PyCO2SYS: marine carbonate system calculations in Python - Humphreys, Matthew P.; Schiller, Abigail J.; Sandborn, Daniel; Gregor, Luke; Pierrot, Denis; van Heuven, Steven M. A. C.; Lewis, Ernie R.; Wallace, Douglas W. R. (Zenodo, 2024)
Changes in v1.8.3 New features Added "dlnfCO2_dT" and "dlnpCO2_dT" results, the theoretical effect of temperature on the natural log of ƒ CO 2 and p CO 2 . Added the PLR18 parameterisation of the carbonic acid constants for sea-ice brines. Default options Reverted default opt_k_carbonic to 10 (i.e., LDK00 ) for consistency with the best practice guide. Bug fixes Updated pyco2.equilibria.p1atm.kH2CO3_NBS_MCHP73 (used for opt_k_carbonic options 6 and 7) to update any salinity values less than 10 –16 to be 10 –16 , because zero salinities give a NaN for K 2 , which causes problems for Autograd. This should not make any practical difference, because the parameterisation is only valid for salinities above 19. Added opt_pressured_kCO2 to results dict and incorporated it correctly into the uncertainty propagation functions. Technical Updated from building with setup.py to pyproject.toml.